Fermentation quality, bacterial community, and aerobic stability of ensiling Leymus chinensis with lactic acid bacteria or/and water after long-term storage - Xu, Haiwen; Xue, Yanlin; Na, Na; Wu, Nier; Zhao, Yi; Sun, Lin; Qili, Moge; Wang, Tianwei; Zhong, Jin (Frontiers in Microbiology, 2022)
This study aimed to reveal the fermentation quality, bacterial community, and aerobic stability of L. chinensis silage treated with lactic acid bacteria or/and water after long-term storage. Leymus chinensis was harvested at the heading stage, and ensiled with lactic acid bacteria (LAB, L), water (W), or a combination of both (LW) in polyethylene laboratory-scale silos (diameter, 20 cm; height, 30 cm) at a density of 650 kg/m3. As a control silage (CK), untreated L. chinensis silage was also assessed. The samples were taken at 0 d of opening after 300 d of ensiling (CK_0d, L_0d, W_0d, and LW_0d) and at 10 d of opening (CK_10d, L_10d, W_10d, and LW_10d). The fermentation quality, microbial counts, bacterial community, and aerobic stability of the silage were assessed. The CK_0d contained higher pH and aerobic bacteria count, and lower LA and BC concentrations than L_0d, W_0d, and LW_0d (P < 0.05), and the LAB and yeast were only detected in CK at 0 d of opening. Lactobacillus had the most abundance among bacterial genera in all silages at 0 d of opening. Just CK had 2 ℃ above the ambient temperature during aerobic exposure (at 224 h). During aerobic exposure, the pH and microbial counts in CK increased (P < 0.05), and Lactobacillus in L and LW had decreasing abundance (P < 0.05). The CK_10d had higher pH and microbial counts, and lower lactic acid and buffering capacity than L_10d, W_10d, and LW_10d (P < 0.05). At 10 d of opening, the coliform and yeast were just detected in CK, and Lactobacillus also had the most abundance among bacterial genera in all silages at 10 d of opening. Overall, inoculating LAB and adding water improved the fermentation quality and the aerobic exposure of L. chinensis silage after long-term storage. The activities of coliform and yeast during aerobic exposure contributed to the aerobic deterioration of L. chinensis silage without any treating. Lactobacillus dominated the bacterial communities of all silage at 0 d and 10 d of opening. During aerobic exposure, the abundance of Lactobacillus reduced in L. chinensis silage treated with LAB or water.